1990
DOI: 10.2337/diacare.13.3.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acarbose on Carbohydrate and Lipid Metabolism in NIDDM Patients Poorly Controlled by Sulfonylureas

Abstract: The ability of acarbose to lower plasma glucose concentration was studied in 12 patients with non-insulin-dependent diabetes mellitus (NIDDM) who were poorly controlled by diet plus sulfonylurea drugs. Patients were studied before and 3 mo after the addition of acarbose to their treatment program, and a significant improvement in glycemic control was noted. Although the decrease in fasting plasma glucose concentration was modest (12.0 +/- 0.8 to 10.8 +/- 0.3 mM), average postprandial plasma glucose concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 16 publications
(10 reference statements)
2
31
2
1
Order By: Relevance
“…Like viscous soluble fibers, these compounds reduce postprandial blood glucose and insulin excursions. Several investigations have reported increased whole-body insulin sensitivity after treatment with an a-glucosidase inhibitor in obese subjects with glucose intolerance (Calle-Pascual et al, 1996;Chiasson et al, 1996;Meneilly et al, 2000), although others have failed to find such an effect (Schnack et al, 1989;Reaven et al, 1990;Jenney et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Like viscous soluble fibers, these compounds reduce postprandial blood glucose and insulin excursions. Several investigations have reported increased whole-body insulin sensitivity after treatment with an a-glucosidase inhibitor in obese subjects with glucose intolerance (Calle-Pascual et al, 1996;Chiasson et al, 1996;Meneilly et al, 2000), although others have failed to find such an effect (Schnack et al, 1989;Reaven et al, 1990;Jenney et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported modest reductions in plasma glucose and HbA 1c concentrations in response to acarbose treatment [220][221][222]. In the post-prandial state, its effect is more pronounced, reducing the 1-h postprandial glucose concentration by approximately 20% [222].…”
Section: Acarbosementioning
confidence: 99%
“…67,71 Acarbose, an a-glucosidase inhibitor, has also been evaluated for its effect on insulin sensitivity in patients with type 2 diabetes and impaired glucose tolerance, and has yielded conflicting results. [72][73][74][75] It appears that although acarbose does not result in a decrease in insulin resistance, insulin sensitivity probably improves in the long-term as a result of improved metabolic control. Acarbose is currently being evaluated in an international study for its ability to prevent or delay the progression of impaired glucose tolerance to type 2 diabetes.…”
Section: Benefits Of A-lipoic Acid On Whole-body Glucose Metabolism Amentioning
confidence: 99%